2012
DOI: 10.1007/s00114-012-0922-4
|View full text |Cite
|
Sign up to set email alerts
|

Communities of different plant diversity respond similarly to drought stress: experimental evidence from field non-weeded and greenhouse conditions

Abstract: Accelerating rate of species loss has prompted researchers to study the role of species diversity in processes that control ecosystem functioning. Although negative impact of species loss has been documented, the evidence concerning its impact on ecosystem stability is still limited. Here, we studied the effects of declining species and functional diversity on plant community responses to drought in the field (open to weed colonization) and greenhouse conditions. Both species and functional diversity positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
3
19
0
Order By: Relevance
“…For L. corniculatus, Lanta et al. () found BM losses under drought stress in a range comparable to that in the present study. Among investigated legumes here, M. falcata is known for its tolerance towards drought stress, which is likely to be induced by dehydrin accumulation (Close, ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For L. corniculatus, Lanta et al. () found BM losses under drought stress in a range comparable to that in the present study. Among investigated legumes here, M. falcata is known for its tolerance towards drought stress, which is likely to be induced by dehydrin accumulation (Close, ).…”
Section: Discussionsupporting
confidence: 90%
“…() have shown good performance of Onobrychis viciifolia under periodic drought stress when harvested at optimal stages. Under conditions of higher temperatures and drought, another forage legume, Lotus corniculatus , performed well and had a good water‐use efficiency at higher temperatures and drought (Carter, Theodorou, & Morris, ; Kostopoulou & Karatassiou, ; Lanta, Doležal, Zemková, & Lepš, ). Minor forage legumes may have lower moisture requirements than white clover and can remain competitive against less desirable species with high biomass production under drought stress (Gilgen, Signarbieux, Feller, & Buchmann, ; Grant et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the most studied type of extreme, drought, can be short term (mostly weeks or months) with (almost) no precipitation (pulse event, e.g. Lanta, Dolezal, Zemkova, & Leps, ), or long term (months to years) with prolonged precipitation deficits (press event, e.g. Evans, Byrne, Lauenroth, & Burke, ).…”
Section: Causes For Variation In Biodiversity–stability Relationshipsmentioning
confidence: 99%
“…Not all findings support the insurance hypothesis. For example, in a greenhouse experiment, Lanta et al [57] found that high species richness and functional diversity provided less resistance against drought stressed conditions than less diverse species assemblages. The same study found no effect of diversity on community resistance under outdoor experimental conditions.…”
Section: Resultsmentioning
confidence: 99%